2016
DOI: 10.18869/acadpub.jafm.68.225.22889
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of GDI Single-hole and Multi-hole Injector Sprays with Comparison of Numerical Break-up Models and Coefficients

Abstract: In the present study the fuel spray of a gasoline direct injected engine with multi-hole injector is simulated. Simulation inputs data, injection flow rate and spray cone angle are obtained from previous experimental studies. Log-normal distribution with different standard deviation is used for initial droplet size as the primary break-up model in order to reach the agreement between experimental and calculated spray tip penetration.As the first step, only one plume of spray injected into a quiescent air envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…The EBM considers that the chemical reaction timescale is much shorter than the turbulence timescale, so the combustion timescale is determined by the turbulence timescale [16]. The reactants are contained in different vortex clusters (Fig.…”
Section: Eddy Breakup Modelmentioning
confidence: 99%
“…The EBM considers that the chemical reaction timescale is much shorter than the turbulence timescale, so the combustion timescale is determined by the turbulence timescale [16]. The reactants are contained in different vortex clusters (Fig.…”
Section: Eddy Breakup Modelmentioning
confidence: 99%
“…This combined model was validated with the experimental data, and it showed good agreement with the macroscopic and microscopic spray characteristics. Zamani et al (2016) studied the simulation of a spray of GDI multi-hole injector. They concluded that model coefficient validated for single plume could not be used for multi plume spray simulation without modification due to plume-to-plume interactions and pressure drag.…”
Section: Overview Of Research Studiesmentioning
confidence: 99%
“…As an alternative to AMR, mesh refinement in the main spray developing regions based on fixed grids is used in many studies (Beck and Watkins, 2003, Senecal et al, 2003, Gong et al, 2010, Banerjee and Rutland, 2012, Battistoni et al, 2015 to accelerate the calculations and to facilitate the results' convergence. Within this approach the common practice of increasing the mesh resolution of LES Rutland, 2012, Xue et al, 2013) following a "trial and error" approach or tuning the spray coefficients (Xue et al, 2013, Zamani et al, 2016 in order to capture the small scale structures is followed in the above studies. This approach, although gives accurate simulation results, is not predictive and a criterion needs to be established as to what should be the minimum grid requirements at the refinement region for optimum numerical and physical accuracy.…”
Section: Groupsmentioning
confidence: 99%